Targeted Knockout of Eukaryotic Translation Initiation Factor 4E Confers Bymovirus Resistance in Winter Barley - Hoffie, Robert Eric; Otto, Ingrid; Perovic, Dragan; Budhagatapalli, Nagaveni; Habekuß, Antje; Ordon, Frank; Kumlehn, Jochen (Frontiers in Genome Editing, 2021)
The EUKARYOTIC TRANSLATION INITIATION FACTOR 4E (EIF4E) is a well-known susceptibility factor for potyvirus infections in many plant species. The barley yellow mosaic virus disease, caused by the bymoviruses Barley yellow mosaic virus (BaYMV) and Barley mild mosaic virus (BaMMV), can lead to yield losses of up to 50% in winter barley. In autumn, the roots of young barley plants are infected by the soil-borne plasmodiophoraceous parasite Polymyxa graminis L. that serves as viral vector. Upon viral establishment and systemic spreading into the upper parts of the plants, yellow mosaics occur as first symptoms on leaves. In the further course of plant development, the disease entails leaf necrosis and increased susceptibility to frost damage. Thanks to the rym4 and rym5 allelic variants of the HvEIF4E gene, more than two thirds of current European winter barley cultivars are resistant to BaYMV and BaMMV. However, several strains of BaYMV and BaMMV have already overcome rym4- and rym5-mediated resistance. Accordingly, new resistance-conferring alleles are needed for barley breeding. Therefore, we performed targeted mutagenesis of the EIF4E gene by Cas9 endonuclease in BaMMV/BaYMV-susceptible winter barley cv. 'Igri'. Small insertions were generated, resulting in a shift of the translational reading frame, thereby causing the loss-of-function of EIF4E. The mutations occurred in the homozygous state already in the primary mutants. Their progeny proved invariably homozygous and fully resistant to mechanical inoculation with BaMMV. EIF4E knockout plants showed normal growth habit and produced grains, yet exhibited a yield penalty.